How sharing of supporters reveals competition amongst non-profit brands. Issue 3 (12th February 2023) - Faulkner, Margaret; Romaniuk, Jenni; Stern, Philip
ABSTRACT: The traditional method of identifying non-profit competitors places those with similar objectives as forming the competitive set (looking inside out). This research provides a different perspective by looking at supporter behaviour and how this is shared across the non-profit sector (outside in). The research also applies the Duplication of Purchase law to a new context. Four data sets from the US and Australia highlight that the overlap of supporters at cause-based groupings (e.g. children versus animal focused) and brand level (e.g. World Vision versus RSPCA) is largely determined by supporter numbers. This supporter-centric analytic view can highlight key competitors and potential collaborators that would be missed using the traditional inside-out perspective.